Beyond the Isoprene Pattern: Bifunctional Polyene Cyclizations. Issue 24 (24th February 2021) - Feilner, Julian M.; Haut, Franz‐Lucas; Magauer, Thomas
Abstract: Polyene cyclizations are capable of producing molecular complexity in a single step. While classical systems are limited to simple alkyl substitution patterns only, bifunctional polyenes take advantage of the unique reactivity of higher‐functionalized alkenes. Here, we highlight the potential of these variants for the synthesis of structurally complex polycycles involving unprecedented termination steps. We also want to provide a stimulus for the development of novel modes of cyclization that involve bifunctional units to enable efficient synthesis of yet inaccessible natural products. Abstract : Bifunctional polyene cyclizations take advantage of the unique reactivity of higher‐functionalized alkenes in contrast to the common isoprene‐based polyenes. The potential of these systems is highlighted by the synthesis of structurally complex polycycles involving unprecedented cyclization pathways.